2016
DOI: 10.4187/respcare.04319
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Maximum Inspiratory Pressure and Hand-Grip Force in Healthy Young and Middle-Age Individuals

Abstract: BACKGROUND: This study aimed to examine the relationship between hand-grip force and maximum inspiratory pressure (P Imax ) in healthy young and middle-age individuals. METHODS: All individuals underwent assessment of inspiratory muscle strength by maximum inspiratory pressure using a U-type water manometer and evaluation of hand-grip force by a hydraulic hand dynamometer. RESULTS: The correlation of P Imax and hand-grip force was strong (r ‫؍‬ 0.76). A multilinear regression model was built to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
3
15
0
4
Order By: Relevance
“…In the relationship between HGS and pulmonary function, most studies supported that HGS was associated with better lung function in all ages, regardless of sex [13][14][15]25]. A study in adolescents showed that HGS was associated with spirometry, while physical activity was not, and the researchers reported that strength training might benefit healthy lungs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the relationship between HGS and pulmonary function, most studies supported that HGS was associated with better lung function in all ages, regardless of sex [13][14][15]25]. A study in adolescents showed that HGS was associated with spirometry, while physical activity was not, and the researchers reported that strength training might benefit healthy lungs [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some researchers have claimed that HGS is associated with the forced expiratory volume in 1 second (FEV1) in chronic obstructive pulmonary disease (COPD) subjects [12], while other studies have shown that HGS has no association with lung function but may be associated with the quality of life in COPD patients [8,11]. More studies have suggested that HGS is positively correlated with parameters of lung function, such as maximum inspiratory pressure [13], forced vital capacity (FVC), FEV1 [14] and peak expiratory flow rate (PEFR) [7]. A cohort study of healthy adolescents revealed that HGS is associated with pulmonary function, and physical activity is not [15].…”
Section: Introductionmentioning
confidence: 99%
“…18 Solunum problemine sahip hastalarda atelektaziyi tersine çevirme, etkin öksürme ve hava yolu hijyenini sağlama yeteneği MİB ile yakından ilişkilidir. [19][20][21] İnspiratuar ve ekspiratuar kas kuvvetini gösteren ağız içi basınçların, kavrama kuvveti de dahil olmak üzere periferal kas kuvveti ile ilişkili olduğu birçok çalışmada belirtilmiştir. [21][22][23][24] Genç ve orta yaşlı bireylerde yapılan çalışmalarda solunum sistemini değerlendirmeye yardımcı, basit bir değerlendirme yöntemi olan kavrama kuvvetinin, inspiratuar kas kuvvetini (özellikle diyafram kası) ve akciğer volümlerini indirekt olarak yansıttığı gösterilmiştir.…”
Section: Veri Toplama Araçlarıunclassified
“…[19][20][21] İnspiratuar ve ekspiratuar kas kuvvetini gösteren ağız içi basınçların, kavrama kuvveti de dahil olmak üzere periferal kas kuvveti ile ilişkili olduğu birçok çalışmada belirtilmiştir. [21][22][23][24] Genç ve orta yaşlı bireylerde yapılan çalışmalarda solunum sistemini değerlendirmeye yardımcı, basit bir değerlendirme yöntemi olan kavrama kuvvetinin, inspiratuar kas kuvvetini (özellikle diyafram kası) ve akciğer volümlerini indirekt olarak yansıttığı gösterilmiştir. 9, 21,25 Fakat bu durumun sadece sağlıklılarda değil, aynı zamanda kronik obstrüktüf akciğer hastalığı, diyabetes mellitus, fibromiyalji ve kritik hastalık gibi farklı tanılara sahip kişilerde yapılan çalışmalarda da benzer şekilde kavrama kuvvetinin, solunum kas kuvvetinin göstergesi olabileceği bildirilmiştir.…”
Section: Veri Toplama Araçlarıunclassified
“…BUCHMAN et. al., 2008, Equações de referência para PImax e PEmax em idosos brasileirosEm indivíduos saudáveis, jovens e de meia idade, foi demonstrado que existe uma correlação forte e positiva entre PImax e FPP e que a FPP pode ser preditiva em até 80% da relação com a PImax (EFSTATHIOU et al, 2016). Em idosos, a diminuição da força muscular esquelética foi associada com redução na função pulmonar através de medidas de força muscular respiratória, assim como com valores de espirometria.…”
unclassified